2017
DOI: 10.1002/bin.1482
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an informational and behavior change program to increase students' self‐reported energy conservation

Abstract: A systematic evaluation of a program, consisting of sustainability education, self-management strategies, and feedback, to decrease college students' energy use was conducted. During treatment, the experimental group showed increased self-reported energy savings relative to baseline levels and relative to the self-reported energy use of the comparison group who were shown only an instructional video on conserving energy. Treatment gains were maintained at a 2-week follow-up. More participants in the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Other studies could not detect a change in attitude [60] or showed that students' attitudes changed towards anthropocentrism throughout their studies [145]. A similar picture emerges regarding the possible effect of sustainability content exposure on behavior: some studies did report a change towards, for example, pro-environmental behavior [48]. Others could not confirm such a trend [165] or showed that studying majors usually associated with sustainability challenges (e.g., engineering) was a negative predictor of "sustainability behavior" [148].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Other studies could not detect a change in attitude [60] or showed that students' attitudes changed towards anthropocentrism throughout their studies [145]. A similar picture emerges regarding the possible effect of sustainability content exposure on behavior: some studies did report a change towards, for example, pro-environmental behavior [48]. Others could not confirm such a trend [165] or showed that studying majors usually associated with sustainability challenges (e.g., engineering) was a negative predictor of "sustainability behavior" [148].…”
Section: Discussionmentioning
confidence: 91%
“…Piyapong [46] and Robinson [47] investigated the relationship between higher education and pro-environmental agency, measured by selfreported behavior. Several environmentally-oriented studies considered behavior change as an outcome of higher education-for example, Desrochers and Mosher [48] and Wisecup et al [49] explored ways to make students save energy, Ting and Cheng [50] sought to enhance pro-environmental behavior through guided learning, and Filter et al, (2020), investigated the effect of experiencing nature. A number of studies (2.5%, Figure 8) asserted that sustainability is multi-dimensional, only to concentrate on environmental aspects in learning content [51] or measured outcomes, e.g., [52].…”
Section: Sustainabilitymentioning
confidence: 99%